Antimony orthophosphate glasses with large nonlinear refractive indices, low two-photon absorption coefficients, and ultrafast response - Falcao, E. L.; de Araujo, C. B.; Bosco, CAC; Maciel, G. S.; Acioli, L. H.; Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2005)
Antimony glasses based on the composition Sb2O3-SbPO4 were prepared and characterized. The samples present high refractive index, good transmission from 380 to 2000 nm, and high thermal stability. The nonlinear refractive index, n(2), of the samples was studied using the optical Kerr shutter technique at 800 nm. The third-order correlation signals between pump and probe pulses indicate ultrafast response (<100 fs) for all compositions. Enhancement of n(2) was observed by adding lead oxide to the Sb2O3-SbPO4 composition. Large values of n(2)approximate to10(-14) cm(2)/W and negligible two-photon absorption coefficients (smaller than 0.01 cm/GW) were determined for all samples. The glass compositions studied present appropriate figure-of-merit for all-optical switching applications. (C) 2005 American Institute of Physics.